Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Section 10.4 - Adding, Subtracting, and Multiplying Radical Expressions - Exercise Set: 76

Answer

$(\sqrt{x-6}-7)^{2}=x-14\sqrt{x-6}+43$

Work Step by Step

$(\sqrt{x-6}-7)^{2}$ Use the formula for squaring a binomial to evaluate this product. The formula is $(a-b)^{2}=a^{2}-2ab+b^{2}$. In this expression, $a=\sqrt{x-6}$ and $b=7$ Substitute the known values into the formula and simplify if possible: $(\sqrt{x-6}-7)^{2}=(\sqrt{x-6})^{2}-14\sqrt{x-6}+49=...$ $...=x-6-14\sqrt{x-6}+49=...$ $...=x-14\sqrt{x-6}+43$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.